The life of solitude - Petrarca, Francesco 1304-1374 (Baylor University Press, 2023)
Francesco Petrarca (Petrarch, 1304–1374) is universally regarded as one of the greatest Italian poets and considered to be the "Father of Renaissance Humanism." Petrarch is best known for his poetry, and especially for his sonnets, composed in the vernacular Italian dialect of his homeland. But Petrarch was also the author of an extraordinary body of prose works in Latin, including numerous books, essays, and volumes of his letters, which, with Cicero as his model, he collected, edited, and preserved for posterity. Included among these Latin prose works is The Life of Solitude ( De vita solitaria), which Petrarch began during Lent of 1346, and then sent in 1366—after twenty years of reflection, addition, and correction—to its dedicatee. Book I contains an argument for why a life of solitude and contemplation is superior to a busy life of civic obligation and commerce. Book II contains a long enumeration of exemplars of the solitary life drawn from history and literature (and occasionally mythology). Included in Book II are provocative digressions on whether one has an obligation to serve a tyrant and on the failures of contemporary monarchs to recover the holy sites in the East. Petrarch’s solitary life is not an apology for monastic solitude. On the contrary, it contains a strong defense of friendship, the pursuit of virtue, and the roles that both secular and religious literature and philosophy play in human flourishing. This updated edition of Jacob Zeitlin’s 1924 English translation restructures and numbers the text to make it consistent with the best available scholarly editions of De vita solitaria. The volume includes a new introduction by Scott H. Moore, Associate Professor of Philosophy and Great Texts and Assistant Director of the University Scholars Program at Baylor University, which situates Petrarch and the text within the larger traditions of virtue ethics, renaissance humanism, and reflectio
Keywords: Solitude / Religious aspects